Investigation of Durable Bio-polymeric Antimicrobial Finishes to Chemically Modified Textile Fabrics Using Solvent Induction System - Shubham Joshi; Vinay Midha; Subbiyan Rajendran (Tekstilec, 2021)
New technologies and materials required for developing antibacterial textiles have become a subject of inter¬est to the researchers in recent years. This study focuses on the investigation of the biopolymeric antibacterial agents, such as neem, aloe vera, tulsi and grapeseed oil, in the trichloroacetic acid-methylene chloride (TCAMC) solvent used for the pretreatment of polyethylene terephthalate (PET) polyester fabrics. Different PET structures, such as 100% polyester, polyester/viscose, polyester/cotton and 100% texturised, are treated with four different concentrations (5%, 10%, 15% and 20%) of biopolymeric antibacterial finishes. The antibacterial activity of the treated samples is tested against both the Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative) bacteria. Taguchi mixed orthogonal array Design L16 (4^3 2^2) is chosen for an experimental plan to determine the optimum conditions. Among all the fabric samples, the 100% polyester fabric treated with 20% grapeseed oil registers the highest antibacterial activity of 86%, and 73% against S. aureus and E. coli respec¬tively. However, the antibacterial effect is reduced to 37%, and 34% respectively after 10 machine launderings.